Editors’ Introduction: Authority, Plurality, and Public Life in a Changing Asia - Asep Iqbal (Journal of Asian Social Science Research, 2021)
How do societies negotiate authority when familiar institutions are unsettled by environmental pressure, technological change, religious contestation, democratic uncertainty, and the search for public trust? This issue of the Journal of Asian Social Science Research (Vol. 3, No. 1, 2021) invites that question through six studies grounded largely in Indonesia, but relevant to wider Asian debates. The articles examine environmental challenges and the social study of religion; the symbolism of hijab in the Tarbiyah movement; the involvement of the Indonesian National Armed Forces in the Citarum Harum water-governance project; the social dimensions of education in the era of the Internet of Things and the COVID-19 pandemic; higher education, national character, and religious moderation; and public legitimacy in the 2020 West Sumatra regional election. What connects them is not a single topic, but a shared attention to how public life is organized through institutions, beliefs, symbols, policies, technologies, and civic trust.